Kajian penambahan karaginan dari rumput laut (Eucheuma cottoni) terhadap sifat-sifat organoleptik sosis ikan Lele (Clarias gariepinus). - Tyas Wara Sulistyaningrum; - Elita (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
This reseach aims to improve the usability of seaweed (Eucheuma cottoni) as raw material for carrageenan and to determine the influence of carrageenan to the organoleptic properties of catfish (Clarias gariepinus) sausage. The research benefit was an improve processing to obtain carrageenan from seaweed and optimally utilize of seaweed. This study was conducted four month at the Laboratory Processing of Fishery Product, Fisheries Department of Palangka Raya University. Data were collected based on observation of the organoleptic test, include color, flavor, texture and odor. Also based on chemical test which includes a test of moisture content, fat content and protein content. Based on the result of organoleptic test and the result of chemical test on catfish sausage, it can be conclude that the addition of carrageenan from seaweed powder did not affect the sensory quality (include color, flavor, texture and odor). The additional of carrageenan powder affect on the chemical quality that binds moisture and fat content and increase the gelatinization level of protein in catfish sausage. Key words : Eucheuma cottoni, carrageenan, sausage, Clarias gariepinus